The pan-variant potential of light: 425 nm light inactivates SARS-CoV-2 variants of concern and non-cytotoxic doses reduce viral titers in human airway epithelial cells - Nathan Stasko; Leslee Arwood; Nicole Jandick; Derry Spragion; Rachel C. Roberts; Mónica Setién; Ibrahim Henson; Abigail Annas; M. Leslie Fulcher; Marisa Brotton; Larry Kummer; Frank Szaba; et al. (mSphere)
ABSTRACT Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) prolonged the coronavirus disease 2019 (COVID-19) pandemic. The continued development of novel pan-variant therapeutics to treat currently circulating and future VOCs is critically important. Photomedicine may offer broadly applicable, pan-variant treatments. In this study, we show that visible light centered around 425 nm inactivates each of the five SARS-CoV-2 VOC lineages that have been identified by the World Health Organization (Alpha, Beta, Delta, Gamma, and Omicron) in cell-free suspensions in a dose-dependent manner, including bamlanivimab-resistant variants. Specifically, 60 J/cm2 of 425 nm light reduced SARS-CoV-2 titers by >4 log10 relative to unilluminated controls. We observed that 425 nm light inactivates SARS-CoV-2 through restricted entry to host cells. In addition, a non-cytotoxic dosing regimen of 32 J/cm2 of 425 nm light reduced infectious virus titers in well-differentiated air–liquid interface (ALI) human airway epithelial (HAE) cells infected with the Beta, Delta, and Omicron variants that incorporate mutations associated with immune evasion and/or increased transmissibility. Infectious SARS-CoV-2 titers were reduced when dosing began during the early stages of infection or in more established infections. Finally, we translated these findings to the RD-X19, a novel medical device that emits 425 nm light; our results showed that the RD-X19 restricted spike binding to ACE-2 and reduced SARS-CoV-2 titers in cell-free suspensions (by >2 log10) and in the ALI HAE model (by >1 log10). These findings indicate that photomedicine utilizing 425 nm visible light may serve as a novel, pan-variant treatment modality for COVID-19.IMPORTANCEThe continued spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to the emergence of variants that can evade public health measures, including vaccines and therapeutics. Thus, the continued development of broadly applicable measures to supplement current public health measures and standards of care remains critical. Photomedicine is one such approach. In this study, we show that non-ultraviolet visible light can inactivate each SARS-CoV-2 variant of concern (VOC) by preventing entry to host cells. Furthermore, visible light reduced the amount of virus produced in an infection model of the human airway at multiple stages of infection, demonstrating the antiviral capability of visible light. This study provides preclinical support for the development of visible light to serve as a SARS-CoV-2 countermeasure and warrants further investigation.